Study Madani Club and Formation of Professional Competence of Prospective Educators: Studi Madani Club dan Pembentukan Kompetensi Profesional Calon Pendidik - Firdaus, Muhamad Wildan; Mardianto, Mardianto (STAI Publisistik Thawalib Jakarta, 2024)
This study examines the role of the Madani Club Study as a platform for developing the professional competence of prospective Islamic Religious Education educators at the Faculty of Tarbiyah and Teacher Training, State Islamic University of North Sumatra. The focus of the study is how the Madani Club Study helps in improving pedagogical skills and internalizing Islamic values. This study uses a qualitative method with data collection techniques obtained through observation, in-depth interviews, and document analysis related to the Madani Club Study activities. The results of the study indicate that the Madani Club Study is effective in improving students' pedagogical competence through collaborative learning and self-reflection, as well as helping internalize Islamic values ??in the context of modern education. The interaction between students and supervising lecturers in the Madani Club Study also creates an environment that supports personal and social growth. This study emphasizes the importance of extracurricular programs based on collaboration and Islamic values ??to be integrated into the curriculum of Islamic universities in order to prepare prospective educators who are competent in facing the challenges of contemporary Islamic education.